If f (x) = f (3x – 1) for f (x) = x2 – 4x +11, then x =

Question

If f (x) = f (3x – 1) for f (x) = x2 – 4x +11, then x =

in progress 0
Eloise 1 month 2021-09-15T01:11:06+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-15T01:12:34+00:00

    The first one is,

    If f(x) =f (3x-1),

    We may have, x =3x-1

    So, we get

    X= 1/2.

    The second one is,

    We have, f(x) =x^2-4x+11

    Then, we get

    x^2-4x +11= ( 3x-1)^2 -4 (3x-1)+11

    Or, 4 (3x-1) -4x = (3x-1)^2 -x^2

    Or, 4 ( 3x-1-x) = ( 3x-1-x)(3x-1+x)

    Or, 4 (2x-1) =(2x-1)(4x-1)

    Or, (2x-1)( 4-4x+1)=0

    Either,

    2x-1=0 ie x=1/2

    Or,

    5-4x=0 ie. X = 5/4

    Hence, form the above two method we get two possible value for x.

    They are 1/ 2 and 5/4.

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )